Perancangan Game Platformer 2D “Seasonal” Pada Web - Silvana Aprilia; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
“Seasonal” is a 2D game with platformer and single player genres. This game can be played on the web or devices that can access the browser. Game is developed using Unity 2019.4.14f1. Players are required to collect 4 treasure boxes from 4 seasons. Those seasons are Spring, Summer, Autumn and Winter. Testing is done by blackbox testing, alpha testing and beta testing. Alpha testing is tested by the supervisor while beta testing is tested by 48 respondents. The results of beta testing show that